Ventilation rates in recently constructed U.S. school classrooms - Batterman, S.; Su, F.‐C.; Wald, A.; Watkins, F.; Godwin, C.; Thun, G. (Indoor air, 2017)
Low ventilation rates (VRs) in schools have been associated with absenteeism, poorer academic performance, and teacher dissatisfaction. We measured VRs in 37 recently constructed or renovated and mechanically ventilated U.S. schools, including LEED and EnergyStar‐certified buildings, using CO2 and the steady‐state, build‐up, decay, and transient mass balance methods. The transient mass balance method better matched conditions (specifically, changes in occupancy) and minimized biases seen in the other methods. During the school day, air change rates (ACRs) averaged 2.0±1.3 hour−1, and only 22% of classrooms met recommended minimum ventilation rates. HVAC systems were shut off at the school day close, and ACRs dropped to 0.21±0.19 hour−1. VRs did not differ by building type, although cost‐cutting and comfort measures resulted in low VRs and potentially impaired IAQ. VRs were lower in schools that used unit ventilators or radiant heating, in smaller schools and in larger classrooms. The steady‐state, build‐up, and decay methods had significant limitations and biases, showing the need to confirm that these methods are appropriate. Findings highlight the need to increase VRs and to ensure that energy saving and comfort measures do not compromise ventilation and IAQ.